Development and reliability of a patient experience inventory tool for hospitals - Agnes Barden; Nicole Giammarinaro; Natalie Bashkin; Larry Lutsky (The Beryl Institute, 2020)
This study explores the development and reliability testing of the newly developed Patient Experience Inventory for Hospitals (PXI-H). Created as an organizational self-assessment patient experience tool, it guides healthcare leaders in evaluating attitudes and behaviors as well as structures and programs impacting patient experience within a hospital setting. The PXI-H is organized within four pillars: Leadership, Education and Development, Data and Analytics and Patient-and-Family Centeredness, which were determined to be internally consistent based on examining coefficient alphas and the item-total correlations. Principal component analysis also determined items with highest loadings aligned onto the pillars in which there were assigned, confirming the hypothesized factor structure. Experience Framework This article is associated with the Policy & Measurement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Policy%20%26%20Measurement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.